2017
DOI: 10.1103/physreve.95.052607
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and aggregation dynamics of a monolayer of paramagnetic colloids

Abstract: We have developed a tunable colloidal system and a corresponding theoretical model for studying the phase behavior of particles assembling under the influence of long-range magnetic interactions. A monolayer of paramagnetic particles is subjected to a spatially uniform magnetic field with a static perpendicular component and a rapidly rotating in-plane component. The sign and strength of the interactions vary with the tilt angle θ of the rotating magnetic field. For a purely in-plane field, θ=90^{∘}, interacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 86 publications
(93 reference statements)
1
22
0
1
Order By: Relevance
“…For two-dimensional (2D) systems, much previous simulation and theoretical work has shown how short-range attraction combined with longer-range repulsion, and even pure repulsion exhibiting multiscale features such as a "shoulder" at short length scale, can generate a complex plethora of structures in and out of equilibrium, including stripes, chains, clusters, and ordered crystals [12][13][14]. Similar patterns are seen in experimental systems such as magnetic particles and biological membranes [6,[15][16][17] and have been discussed in the general context of geometrically frustrated materials [18]. 2D systems are particularly interesting for applications such as structured membranes, filters, films, coatings, and biological materials.…”
Section: Introductionmentioning
confidence: 81%
“…For two-dimensional (2D) systems, much previous simulation and theoretical work has shown how short-range attraction combined with longer-range repulsion, and even pure repulsion exhibiting multiscale features such as a "shoulder" at short length scale, can generate a complex plethora of structures in and out of equilibrium, including stripes, chains, clusters, and ordered crystals [12][13][14]. Similar patterns are seen in experimental systems such as magnetic particles and biological membranes [6,[15][16][17] and have been discussed in the general context of geometrically frustrated materials [18]. 2D systems are particularly interesting for applications such as structured membranes, filters, films, coatings, and biological materials.…”
Section: Introductionmentioning
confidence: 81%
“…50, where it has been shown that three-body interactions become significant (up to ∼60% comparing to the pair energy) at distances smaller than two particle diameters, while the many-body effects of higher orders can be neglected. 32,35,50 Therefore, the relevant experimental conditions can be satisfied for 2D suspensions of particles having a magnetic core and nonmagnetic shell and exposed to rapidly rotating in-plane magnetic fields. The thickness of the nonmagnetic shell should not be (at least) about a half of the core diameter.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Two-dimensional (2D) colloidal crystals self-assembled in external fields can act as seeds for 3D structures used in photonics [4][5][6][7][8] as well as for porous media and membranes used for photocatalysis, electrochemical energy storage and conversion, and chemical applications. [9][10][11][12][13] Although tunable interactions can be achieved in different ways (including optical, chemical, and flow-mediated mechanisms 2 ), the use of electric [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and magnetic 16,[30][31][32][33][34][35][36][37][38][39][40][41] fields is among the most promising due to their technological flexibility, the long-range character of the obtained interactions, and the ability to change them in situ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this chapter, we review the studies of static structural and dynamical properties in colloidal magnetic fluids, which provide a comprehensive description of their bulk phase behavior at thermal equilibrium. Presently, model magnetic colloidal systems can be prepared with tunable interaction among particles of the hard sphere and longrange dipolar types [11][12][13][14], especially the colloidal system constituted of micronsize polystyrene spheres that are electrically charged and dispersed in organic solvents [11]. In such a system, particles acquire an induced electric dipole moment under the external static electric field.…”
Section: Introductionmentioning
confidence: 99%